2012
DOI: 10.1016/j.jviscsurg.2012.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Acute appendicitis in pregnancy: Specific features of diagnosis and treatment

Abstract: Acute appendicitis puts both maternal and fetal prognosis at risk. Management should be prompt and undertaken by a multidisciplinary team approach. Morbidity and mortality are not negligible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 21 publications
1
24
1
3
Order By: Relevance
“…[21,22] Terzi et al found rate of 13% [14] and Miloudi et al reported negative appendectomy rate of 3.4%. [23] Present study finding of 30% rate is higher than literature findings, but may be explained by inability to perform MRI or presence of physical findings that indicated urgent exploration.…”
Section: Discussioncontrasting
confidence: 79%
“…[21,22] Terzi et al found rate of 13% [14] and Miloudi et al reported negative appendectomy rate of 3.4%. [23] Present study finding of 30% rate is higher than literature findings, but may be explained by inability to perform MRI or presence of physical findings that indicated urgent exploration.…”
Section: Discussioncontrasting
confidence: 79%
“…Appendicitis during pregnancy is attended by a significant obstetrical risk, as is demonstrated in this report and in other published series [2]. Thus, the risk of premature labor and delivery and of low-birth weight as well as other obstetrical complications is increased after acute appendicitis.…”
Section: Prognostic Factors Related To Pregnancysupporting
confidence: 75%
“…In a recent literature review [3], complicated appendicitis was more often associated with fetal loss than was simple unperforated appendicitis (12.1% vs. 3.4%, P = 0.0027). Similarly, in the Taiwanese register of appendicitis during pregnancy, patients who had been hospitalized for abdominal pain during the preceding days had an increased risk of premature delivery (30.8% vs. 11%, P = 0.002) and of low birth weight (38.5% vs. 21.9%, P = 0.046) [2]. The diagnosis of appendicitis should always be considered in any pregnant women who presents with acute abdominal pain.…”
Section: Prognostic Factors Related To Pregnancymentioning
confidence: 99%
“…cute appendicitis is one of the most common indications for abdominal surgery in children, adults, and pregnant women (1)(2)(3)(4)(5). An accurate diagnosis is important to minimize perforation and rates of appendectomy with negative results.…”
mentioning
confidence: 99%